PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM), TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2009 – 2013 (Students' Journal of Accounting and Banking, 2014)
An investor buying the current number of shares in the hope of gain from stock price increases or the number of future dividends, in return for the time and risk associated with these investments. This study aims to examine and analyze the effect of return on assets, return on equity and net profit margin of the Company's stock price on Banking in Indonesia Stock Exchange Period 2009-2013. The population in this study were all commercial banks listed on the Indonesia Stock Exchange (IDX) 2009-2013. The sampling technique used purposive sampling. Based on purposive sampling obtained a sample of 22 companies. The data analysis technique used is multiple linear regression analysis. Based on the test results it can be concluded that the return on assets variable has positive effect on stock prices. Variable return on equity and net profit margin has no effect on stock prices at a bank that went public in the Indonesia Stock Exchange.Keywords: return on assets, return on equity, net profit margin and stock price